Find the exact solution to: ln(x) + ln(7) = ln(21)

Log rules:

log(a) + log(b) = log(ab)

so, in this case, we must find x such that 7x = 21

thus x = 3

similarly, log(a) - log(b) = log(a/b)

rearranging the original equation we get:

ln(x) = ln(21) - ln(7)

so x = 21/7 = 3

Answered by Bryan P. Maths tutor

6180 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Which value of x gives the greatest value of "-x^2+8x-6"


Differentiate x^2+6x+1


The mass of a substance is increasing exponentially. Initially its mass is 37.5g, 5 months later its mass is 52g. What is its mass 9 months after the initial value to 2 d.p?


use the substitution u=2+ln(x) to show that int(e,1(ln(x)/x(2+ln(x)^2))dx)=p+ln(q) , where p and q are rational numbers.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences